Worship with one accord : where liturgy and ecumenism embrace - Wainwright, Geoffrey, 1939- (Oxford University Press, 1997)
The historical course of Christianity in the 20th century has been strongly marked by the Ecumenical Movement and the Liturgical Movement, and often these currents for the recovery of the Church's unity and the renewal of its worship have flowed together. In this book Geoffrey Wainwright draws on his three decades of active participation in both movements to offer a theologically informed account of what has been at stake in them, what their achievements have been, and what tasks remain for them to accomplish.; This book is intended for students and scholars of Christian theology, liturgics, and contemporary Christianity.